2002
DOI: 10.1046/j.1365-313x.2002.01454.x
|View full text |Cite
|
Sign up to set email alerts
|

NPP1, a Phytophthora‐associated trigger of plant defense in parsley and Arabidopsis

Abstract: SummaryActivation of non-cultivar-specific plant defense against attempted microbial infection is mediated through the recognition of pathogen-derived elicitors. Previously, we have identified a peptide fragment (Pep-13) within a 42-kDa cell wall transglutaminase from various Phytophthora species that triggers a multifacetted defense response in parsley cells. Many of these oomycete species have now been shown to possess another cell wall protein (24 kDa), that evoked the same pattern of responses in parsley a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
313
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 274 publications
(324 citation statements)
references
References 68 publications
(154 reference statements)
7
313
0
4
Order By: Relevance
“…Interrogation of the M. grisea genome for putative effector proteins revealed three families of putatively secreted, cysteinerich polypeptides (clusters 180, 360 and 641) and a protein family with similarity to the necrosis-inducing peptide of Phytophthora infestans (NPP1, pfam05630) 29 . As described above, cysteine-rich polypeptides are recognized as PAMPs, as exemplified by the C. fulvum-tomato interaction 30 .…”
Section: Fungal Effectors and Pampsmentioning
confidence: 99%
“…Interrogation of the M. grisea genome for putative effector proteins revealed three families of putatively secreted, cysteinerich polypeptides (clusters 180, 360 and 641) and a protein family with similarity to the necrosis-inducing peptide of Phytophthora infestans (NPP1, pfam05630) 29 . As described above, cysteine-rich polypeptides are recognized as PAMPs, as exemplified by the C. fulvum-tomato interaction 30 .…”
Section: Fungal Effectors and Pampsmentioning
confidence: 99%
“…The founding member of this family was isolated in 1995 from the culture medium of Fusarium oxysporum based on its capability to trigger both ethylene production and necrosis in numerous dicotyledonous plants, therefore named NEP1 (necrosis and ethylene inducing peptide 1). 1 Follow-up studies identified a number of oomycete and bacterial NLPs, such as PaNIE from Pythium aphanidermatum (NLP Pya ), 2 NPP1 from Phytophthora parasitica (NLP Pp ), 3 PsojNIP from Phytophthora sojae (NLP Ps ) 4 or NIP from Pectobacterium carotovorum subsp. carotovorum (NLP Pcc ) 5 that elicit diverse defense reactions in dicots.…”
Section: Nlps-from Elicitors To Toxinsmentioning
confidence: 99%
“…These responses resemble to a great extent those triggered by the well-studied PAMP flg22. [1][2][3][4]8,9 Furthermore, NLPs show a broad taxonomical distribution with high conservation.…”
Section: Nlps-from Elicitors To Toxinsmentioning
confidence: 99%
See 2 more Smart Citations